Conceptualizing Interactions between SDGs and Urban Sustainability Transformations in Covid-19 Times - Krellenberg, Kerstin (2021)
Given the potential of cities to contribute to a more sustainable world as framed by the Sustainable Development Goals (SDGs) of the UN 2030 Development Agenda, this article focuses on Urban Sustainability Transformations. We take a closer look at the potentials, contradictions and challenges that SDG implementation in cities involves in light of the current Covid-19 pandemic. We argue that SDG implementation needs to consider these global challenges in order to pursue its transformative approach. As a starting point we take SDG 11 and its subtargets to achieve resilient cities and communities, with a focus on German cities. The article will thus contribute to the discussion on the constraints associated with implementing SDGs in cities, given the multiple challenges and actors involved, and the complexity this implies for Urban Sustainability Transformations.